Hubungan Perilaku Kesehatan Orang Tua Terhadap Tingkat Keparahan Karies Anak Usia 4-6 Tahun TK Karang Asem - Paramita, Ade Listha Anindya; , Dwi Kurniawati, S.KG, MPH; , drg. Suyadi (2015)
Background: Dental caries is a disease of hard tissue of teeth marked with a progressive damage of enamel and dentin. Caries in the primary dentition of children is strongly associated with parent factor's. Parental behavior of teeth and mouth health is affected caries incident of their children. Purpose: Purpose of the research is to know correlation of health behavior of parent and caries severity level of 4-6 years old children. Method: The research is an analytical-observational one with Cross Sectional approach. Sample of the research is taken by using simple random sampling. Respondents of the research are 57 individuals consisting of 20 males and 37 females. Severity level of caries is measured by using Caries Severity Index (CSI) and healthy behavior of parent is measured by using a structured questionnaire. Questionnaires were distributed through children who were attending Karang Asem Kindergarten to their parents. The children were examined for severity level of caries. Data of the research was analyzed by using Pearson test (parametric test). Results: Pearson test indicated correlational value of -0.372 with significance of 0.004. Averaged severity level of caries among the children was categorized as moderate and average health behavior of parents was categorized as good. Conclusion: A significant correlation between health behavior of parents and severity level of caries among children of Karang Asem Kindergarten was found meaning that the higher health behavior of parent, the lower severity level of caries.